Functionalized layered double hydroxide-based epoxy nanocomposites with improved flame retardancy and mechanical properties. Issue 13 (7th April 2015) - Kalali, Ehsan Naderi; Wang, Xin; Wang, De-Yi
<x xml:space="preserve">Abstract</x> Aiming at developing highly efficient nano fire retardants and fire retarding epoxy resins, a series of functionalized layered double hydroxides (LDHs) based on a multi-modifier system have been developed. These functionalized LDHs were used as novel nano flame-retardants for bisphenol epoxy resins and compared with unmodified LDHs.